Acerca de la Etnoarqueología en América del Sur - Politis, Gustavo Gabriel (2002)
Despite all of the potential that South America has for ethnoarchaeo-logical research, the development of Ethnoarchaeology is still very limited in this region. Only in the last decade ethnoarchaeological projects have grown, specially among South American archeologists. The present article revises the conceptual foundations of this field of study and analyses its present tendencies in South America. A discussion of the field's potential is made, not only as to what it can bring to the study of the relationship between human conduct and material derivations, but also as to the conditions in which we can expect to find certain types of archeological data. At last, the present article explores the uses that can be made out of Ethnoarchaeology in the study of other forms of thought and other patterns of rationality - forms and patterns that are hard to be identified in archeological data but are essential to understanding fundamental aspects of past societies.